Selection of Bacteria from Mamuju’s NORM as Uranium and Thorium Bioleaching Agents - Indryati, S.; Mujiyanto, A.; Widana, K. S.; Hidayat, A. E.; Rahma, F. J.; Shabirah, C. A.; Laksmana, R. I.; Pratama, A. A.; Trinopiawan, K.; Prassanti, R.; Purwanti, T.; Putra, A. W.; Sukadana, I G.; Sugoro, I. (National Research and Innovation Agency, 2025)
Natural materials that can cause increased radiation exposure to the surrounding environment are called Naturally Occurring Radioactive Materials (NORM). NORM contains uranium and thorium, critical elements with strategic and economic value. Conventional separation methods include chemical leaching and partial precipitation with strong acids and bases. These methods require large costs and produce waste harmful to the environment. This study explores bioleaching as an efficient and eco-friendly alternative to address these limitations. The indigenous bacteria used in bioleaching were isolated directly from NORM in Mamuju. This study aims to isolate, select, and evaluate bacteria from NORM as potential bioleaching agents. The methodology of this study includes NORM characterization, bacterial isolation and selection, molecular identification, and resistance testing of selected bacteria. The study successfully isolated eight bacterial strains from NORM, among which isolate L0A demonstrated the highest bioleaching potential. After five days of incubation, L0A achieved uranium and thorium concentrations of 2.508 mg/L and 10.5946 mg/L, respectively. Molecular identification revealed that L0A belongs to Bacillus sp. These findings demonstrate the potential of Bacillus sp. L0A is a bioleaching agent, paving the way for developing efficient, sustainable, and environmentally friendly methods for extracting valuable radioactive elements from NORM.